2017
DOI: 10.1038/tp.2017.122
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and vascular remodeling in the ventral hippocampus contributes to vulnerability to stress

Abstract: During exposure to chronic stress, some individuals engage in active coping behaviors that promote resiliency to stress. Other individuals engage in passive coping that is associated with vulnerability to stress and with anxiety and depression. In an effort to identify novel molecular mechanisms that underlie vulnerability or resilience to stress, we used nonbiased analyses of microRNAs in the ventral hippocampus (vHPC) to identify those miRNAs differentially expressed in active (long-latency (LL)/resilient) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 101 publications
(171 reference statements)
4
65
0
2
Order By: Relevance
“…Many more animals were classified as passive copers than active copers. In past work, using this analysis has yielded similar segregation of groups (Chen et al, 2015;Pearson-Leary et al, 2017, 2019Grafe et al, 2018). Moreover, three additional animals had unreadable telemeter recordings (see next section).…”
Section: Social Defeat Paradigmmentioning
confidence: 63%
See 1 more Smart Citation
“…Many more animals were classified as passive copers than active copers. In past work, using this analysis has yielded similar segregation of groups (Chen et al, 2015;Pearson-Leary et al, 2017, 2019Grafe et al, 2018). Moreover, three additional animals had unreadable telemeter recordings (see next section).…”
Section: Social Defeat Paradigmmentioning
confidence: 63%
“…In different individuals, or under different conditions, either active coping, characterized by the fight or flight response, or passive coping, characterized by immobility and withdrawal, can occur during exposure to stressors (Engel and Schmale, 1972;Koolhaas et al, 1999;Southwick et al, 2005;Wood and Bhatnagar, 2015). The present experiments used an animal model of repeated social defeat stress in which active and passive coping strategies dichotomize into either a resilient or vulnerable trait, respectively, as assessed post hoc by various neuroendocrine measures, behavioral tests (Wood et al, 2010;Chen et al, 2015;Wood and Bhatnagar, 2015;Finnell et al, 2017), and markers of inflammation (Pearson-Leary et al, 2017, 2019. Understanding whether such differences in coping strategy are associated with the subsequent development of sleep disturbances akin to those reported in PTSD may help to provide a basis for examining the mechanisms by which traumatic stress affects sleep in vulnerable individuals.…”
Section: Introductionmentioning
confidence: 99%
“…We describe here a molecular framework in which cldn5-related epigenetic modifications and transcriptional changes in the NAc lead to stress resilience or vulnerability and depression. In rodents, depression-like behaviors have been associated with increased BBB permeability (7,8) while vascular dysfunction was not observed in those displaying stress resiliency (7,24). However, the cellular and molecular mechanisms involved in this process remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying immune environment alters the interaction between stress and inflammatory processes, thus contributing to the risk of depressive symptoms 36,37 . In our study we found that the levels of IL4 were decreased in the hippocampus of HS mice, but increased in LS mice.…”
Section: Discussionmentioning
confidence: 99%